2016
DOI: 10.1177/1073858415595004
|View full text |Cite
|
Sign up to set email alerts
|

Regional Homogeneity

Abstract: Much effort has been made to understand the organizational principles of human brain function using functional magnetic resonance imaging (fMRI) methods, among which resting-state fMRI (rfMRI) is an increasingly recognized technique for measuring the intrinsic dynamics of the human brain. Functional connectivity (FC) with rfMRI is the most widely used method to describe remote or long-distance relationships in studies of cerebral cortex parcellation, interindividual variability, and brain disorders. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(131 citation statements)
references
References 99 publications
2
127
0
2
Order By: Relevance
“…Other studies have also reported relationships between ReHo and many factors including age24, gender2425, and intelligence26. These findings indicated that the localized brain connectivity is associated with the physiological, pathological, and psychological changes in human brain27.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Other studies have also reported relationships between ReHo and many factors including age24, gender2425, and intelligence26. These findings indicated that the localized brain connectivity is associated with the physiological, pathological, and psychological changes in human brain27.…”
mentioning
confidence: 76%
“…Another methodological concern is the 3-dimensional algorithm we used to compute ReHo. As cortical surface has complex folding patterns (sulcus and gyrus), the neighbouring voxels defined in 3d ReHo algorithm may not be the real neighbours in geodesic distance27, introducing some confounding effects. Therefore, in future studies, it could be beneficial to explore ReHo and its dynamics using surface-based 2d-ReHo algorithm2733.…”
Section: Discussionmentioning
confidence: 99%
“…To optimize the trade-off between mitigation of partial volume effects and generation of Gaussian random fields, we chose 27 voxels to calculate the ReHo, as it is more appropriate for covering all directions in 3D space. [13] We implemented the computation of ReHo in individual native spaces to avoid multiple confounding sources introduced by head motion, imperfect image registration, and non-neural physiological processes. [13] For standardization purposes, individual ReHo maps were divided by their global average within the whole-brain mask.…”
Section: Methodsmentioning
confidence: 99%
“…[13] We implemented the computation of ReHo in individual native spaces to avoid multiple confounding sources introduced by head motion, imperfect image registration, and non-neural physiological processes. [13] For standardization purposes, individual ReHo maps were divided by their global average within the whole-brain mask. Then, spatial smoothing was performed using a 4 mm full-width at half-maximum (FWHM) Gaussian kernel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation